IT for Business (IT4B) : From Genesis to Revolution, a Business and IT Approach to Digital Transformation. - Johnson, Brian; Zondervan, Walter (Ely : IT Governance Ltd, 2018)
This book reads like a conversation on IT service management. Rather than reinventing traditional IT frameworks or methods, IT4B provides a coherent understanding of digital readiness for your enterprise. It offers insight and coaching, rather than ready-made advice because not all businesses work best with a one-size-fits-all approach.
Managing contracts and service performance -- What is contract management? -- Intelligent/informed customer capability -- Managing multiple interfaces -- Who is involved? -- Critical success factors -- Foundations for contract management -- Other issues -- Implementation &amp -- Transition -- Deployment &amp -- Maintenance -- Checklist/activities -- Requirements -- Design -- Build -- Deploy -- Operate -- Service &amp -- Support -- Service &amp -- Support for the business -- Supporting the user of digital services -- Chapter Seven: Digital Readiness and Innovation -- Chapter Eight: Mythical Airlines Case Study -- Mythical Airlines Ltd -- The IT interaction -- Think about service characteristics -- Partners -- Key points -- Transactions -- Training and documentation -- Chapter Nine: The Bottom Line -- Transformation -- The key drivers of transformation -- Define digital -- Appendix A: Theories about organisational change -- Why IT4B? -- Appendix B: Useful pointers in formulating business and IT strategy -- General -- Requirement focus -- Demand focus -- Purchasing approach -- Service definition -- Current service performance -- Degrees of integration -- Technology familiarity and maturity -- Appendix C: A communications strategy -- Appendix D: Skills -- Successful delivery skills framework -- Possible maturity levels -- How the framework could be designed -- How to use the framework -- Leadership -- Finance -- Programme and project delivery -- Specific responsibilities -- Appendix E: Thoughts about testing the design of services -- Test management -- Appendix F: Performance -- Design or procurement details -- Effectiveness -- Performance -- Appendix G: Maintenance -- Optimise -- People -- Business process -- Technology -- Further Reading.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Information technology; Knowledge management; New products; Technological innovations; Creative ability in business; Creative thinking; Electronic books